PEMBERANTASAN MAFIA TANAH DENGAN MENGGUNAKAN ISTRUMEN HUKUM PIDANA DI INDONESIA - Yunawati Karlina; Irwan Sapta Putra (Res Justitia : Jurnal Ilmu Hukum, 2022)
Recently, the people of Indonesia were shocked by the news about a top artist Nirina Zubir who had become a victim of the land mafia, as a result, she had to lose her parents' land assets, which was estimated at Rp. 17,000,000,000 (seventeen billion rupiah).  Law enforcement, in this case the Indonesian National Police, has taken a quick and precise step in exposing the crime that happened to the victim of the artist Nirina Zubir  by arresting the perpetrators of the land mafia consisting of his assistants and a notary / PPT who helped multiply the land rights and houses belonging to the artist's parents.   With the rise of land mafia crimes, the question arises how to overcome the land mafia crimes and what are the right steps to eradicate the land mafia. For this reason, this study discusses issues related to eradicating land mafia using criminal law instruments.  The research method in this study uses a statutory approach, a historical approach, and a case approach. While the Type of Research This research is normative legal research. Sources of data in this study using primary, secondary and tertiary data sources. Data collection techniques by means of document/library studies, data analysis is carried out by qualitative juridical methods.  Eradication of land mafia by using criminal law instruments is currently the right method because it can quickly uncover land mafia crimes, we can see this from the disclosure of cases experienced by the meaning of Nirina Zubir  where the police have determined the suspects for the land mafia, but in the future it is necessary to take systematic and organized steps so that the land mafia crime can be eradicated by cooperating with law enforcement agencies and the ministry of ART and related ministries and high state institutions and also requires strict supervision and in the future it is necessary to form a statutory regulation which specifically regulates crimes related to the land mafia